COVID-19-Associated Pulmonary Aspergillosis in Patients with Acute Leukemia: A Single-Center Study - Jovan Rajic (MDPI AG, 2021)
Patients with coronavirus disease 19 (COVID-19) have increased susceptibility to secondary respiratory infections including invasive pulmonary aspergillosis (IPA). COVID-19-associated pulmonary aspergillosis (CAPA) is difficult to diagnose and can be associated with increased mortality especially in severe immunodeficiency such as hematological malignancies. Our study evaluates IPA in COVID-19 patients defined as COVID-19-CAPA among patients with acute leukemia (AL). A retrospective single-center study analyzed 46 patients with COVID-19 infection and acute leukemia, admitted to the Clinic for Haematology, Clinical Center of Serbia, Belgrade between the 2 April 2020 and 15 May 2021. During hospitalization, all participants were diagnosed with probable IPA according to the previous consensus definitions. Positive serology and galactomannan (GM) detection values in bronchoalveolar lavage (BAL) and serum were used as microbiological criteria. COVID-19 associated probable IPA was found in 22% (9/41) tested patients, where serum GM and IgM anti-Aspergillus antibodies were positive in 12% (5/41) and 10% (4/41) had positive serology for aspergillosis. One patient died while eight recovered during follow-up. Our study showed that COVID-19 might be a risk factor for IPA development in patients with AL. Early diagnosis and prompt treatment are required as reported mortality rates are high.